A case of mistaken identity: an enthesitis-related arthritis case report - Blackard, Michael F.; Patel, Prapti A.; Pandya, Divya A.; Gupta, Manish K.; Pandya, Abhijit S. (International Journal Of Community Medicine And Public Health, 2021)
Juvenile idiopathic arthritis is the most common inflammatory rheumatological condition affecting children. The condition stems from the inability of the immune system to discriminate between self and not-self leading to inappropriate immune reactions against joints. The different subtypes are differentiated by the number of joints involved and the presence or absence of certain exclusion factors. Due to overlapping diagnostic criterion and range of clinical presentation, diagnosis can be a difficult task. Our patient initially presented with joint swelling without pain that was initially diagnosed with traumatic swelling that later was considered to be of an infectious etiology. A biopsy revealed synovitis but current treatment for traumatic and infectious causes continued to fail. Finally, an additional joint showed inflammation leading to additional testing that uncovered that the patient was positive for HLA-B27 as well as a first degree relative with ankylosing spondylitis. This coupled with the inflammatory biopsy findings led to the diagnosis of juvenile idiopathic arthritis. The identification of an HLA-B27 positive patient is important as this population has been shown to have low rates of remission, resistance to certain treatments used for juvenile idiopathic arthritis, specifically DMARDS and corticosteroids which are often first line treatments for juvenile idiopathic arthritis. The HLA-B27 patient population has also been shown to progress to axial involvement and joint destruction leading to earlier need for arthroplasties. As early identification is important in the determination to begin biologic treatments early in the disease course, physician should maintain a clinical suspicion for JIA when dealing with swollen joints in the pediatric population.